Recent advances and emerging therapies in anaplastic thyroid carcinoma - Cabanillas, Maria E. (F1000Res, 2018)
Anaplastic thyroid cancer is a rare and aggressive thyroid cancer with an overall survival measured in months. Because of this poor prognosis and often advanced age at presentation, these patients have traditionally been treated palliatively and referred for hospice. However, recent progress using novel therapies has energized the field, and several promising clinical trials are now available for these patients. This review will highlight this progress and the potential treatments that could pave the way to improved outcomes and quality of life for patients with this disease.